2017
DOI: 10.1177/2040620717720861
|View full text |Cite
|
Sign up to set email alerts
|

Review of recombinant anti-haemophilic porcine sequence factor VIII in adults with acquired haemophilia A

Abstract: Acquired haemophilia A (AHA) is a rare, serious bleeding disorder most often encountered in elderly patients. The mainstay of haemostatic management is with bypassing agents (BPAs) including recombinant activated factor VII (rFVIIa) and activated prothrombin complex concentrates (aPCCs). Their major limitation is incomplete efficacy, potential risk for thrombosis and the lack of routine laboratory assays for monitoring treatment response. Plasma-derived porcine FVIII (pd-pFVIII, Hyate C), first used in the 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 20 publications
0
47
0
1
Order By: Relevance
“…The adult patient population was similar to the one we previously described with a modification to the Markov decision analytic model (Fig. ) that was developed using Microsoft Excel (Microsoft Corporation, Redmond, WA, USA) so that these hypothetical hospitalized, high‐titred (>5 Bethesda units [BU]) AHA patients with bleeding could also be treated with rpFVIII (represented by Obizur, Baxter, Westlake Village, CA, USA) in addition to aPCC (represented by FEIBA, Shire, Lexington, MA, USA) and rFVIIa (represented by NovoSeven, Novo Nordisk, Plainsboro, NJ, USA) . In brief, regardless of the treatment, similar to our previous study, the model allowed the patients to be transitioned into four different health states: (1) continuous bleeding, (2) thrombosis, (3) stop bleeding and (4) death .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adult patient population was similar to the one we previously described with a modification to the Markov decision analytic model (Fig. ) that was developed using Microsoft Excel (Microsoft Corporation, Redmond, WA, USA) so that these hypothetical hospitalized, high‐titred (>5 Bethesda units [BU]) AHA patients with bleeding could also be treated with rpFVIII (represented by Obizur, Baxter, Westlake Village, CA, USA) in addition to aPCC (represented by FEIBA, Shire, Lexington, MA, USA) and rFVIIa (represented by NovoSeven, Novo Nordisk, Plainsboro, NJ, USA) . In brief, regardless of the treatment, similar to our previous study, the model allowed the patients to be transitioned into four different health states: (1) continuous bleeding, (2) thrombosis, (3) stop bleeding and (4) death .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, after the approval, there have been several studies describing its successful real‐world usage . Unlike aPCC or rFVIIa (which are given as fixed doses without routine monitoring and hence, theoretically, can be associated with thrombotic complications), the dosage of rpFVIII can be adjusted based on the measured peak and trough level of factor VIII . Therefore, this can be an advantage in using rpFVIII.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recombinant porcine factor VIII (rpFVIII) has been approved by the Food and Drug Administration and has shown positive results in real-world practice. 9 FVIIa is most frequently used as first-line therapy. Studies showed that rFVIIa and APCC have an overall efficacy of 90%, [10][11][12] while rpFVIII has been shown in small studies to have an efficacy of around 86%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that rFVIIa and APCC have an overall efficacy of 90%, [10][11][12] while rpFVIII has been shown in small studies to have an efficacy of around 86%. 9 Desmopressin can be useful in treating minor bleeding as it increases the amount of clotting FVIII and tissue plasminogen activator. However, the use of desmopressin should not delay the use of a bypassing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment goals for AHA comprise hemostasis and inhibitor eradication [ 1 , 3 ]. To control bleeding, previous authors have advocated the use of bypassing agents, including recombinant activated factor VII (rFVIIa; NovoSeven®) and/or activated prothrombin complex concentrate (APCC; Feiba®), as well as recombinant porcine FVIII [ 5 ]. Challenges in the management of AHA in elderly patients include (1) delayed diagnosis probably due to the relatively low prevalence of AHA, differentiation from other bleeding disorders, and the fact that patients typically present to nonhematologists; (2) the presence of comorbid disease often complicates the administration of prednisolone as well as the selection of hemostatic and immunosuppressive agents; (3) frequent need of anticoagulants in association with poor venous access; (4) high costs of therapy; and (5) thromboembolic risk when FVIII returns to normal.…”
Section: Introductionmentioning
confidence: 99%